Strategies to Educate Traditional Market Traders Based on Information Technology in Beringharjo Market, Yogyakarta City - Nelly Tiurmida; Tomi Agus Triono; Utami Sulistiana; Sugiyanto Sugiyanto (Universitas Muhammadiyah Yogyakarta, 2022)
The research strategy educates traditional market traders based on information technology using a qualitative approach to case studies. Data were collected through observation, interviews and documentation studies. The validity of the data is processed through tests of the degree of trust, transferability, dependence and certainty. Informance is determined by purposive sampling techniques, then the data is analyzed following qualitative rules. The research aims to explore how the Trade Office educates market traders in Pasar Beringharjo through a digitalization program. The results showed that the Department of Trade in educating market traders based on information technology uses strategies: a) external party cooperation, training, mentoring, developing insights and involving trader family members for traders who are constrained by brainware. The driving factors in educating information technology-based traders include: high participation of information technology companies, demands for government and merchant needs, government awareness of IT developments to preserve and develop the market, covid 19 outbreak, high merchant commitment supported by mobile phone communication tools. The inhibiting factors in educating information technology-based traders include the hardware and software owned by merchants, not all smartphones, as well as merchant culture that is still conventional. The results of the merchant market digitization program maintain commitment and are able to carry out online transaction systems with various application models such as Gopay or e-wallet, QRIS, E-Retribution, LinkAja, Grocery, InMobi, Titipku, and Semar by scanning barcodes and other eknik t.